Liver Metabolomics Reveals the Effect of Lactobacillus reuteri on Alcoholic Liver Disease - Zheng, Tian-xiang; Pu, Shi-lin; Tan, Peng; Du, Yi-chao; Qian, Bao-lin; Chen, Hao; Fu, Wen-guang; Huang, Mei-zhou (Frontiers in Physiology, 2020)
Alcoholic liver disease (ALD), a type of chronic liver disease that is prevalent worldwide, is still identified to have a poor prognosis despite many medical treatment protocols. Thus, it is urgent to develop and test new treatment protocols for ALD. Lactobacillus reuteri (L. reuteri) has been widely used in the clinical treatment of digestive system diseases, but studies on the protective effect of L. reuteri on ALD are considered to be rare. Therefore, in the present study, we examined the effect of L. reuteri on ALD and provide data that are significant in the development of new treatment protocols for ALD. An ALD model has been established in C57BL/6J mice treated according to the Gao-binge modeling method. Mice in the treatment group were administered with L. reuteri. Hematoxylin and eosin (H&E) staining, oil red O staining, immunohistochemistry, and biochemical analyses were performed to detect the phenotypic changes in the liver among mice in the different treatment groups. L. reuteri treatment reversed inflammatory cell infiltration and lipid accumulation. Moreover, AST, ALT, TG, and TCH levels were also reduced in the probiotics-treatment group. Five candidate biomarkers were found in the liver metabolites of different treatment groups by UPLC/QTOF-MS and a multivariate analysis. Several fatty acid metabolic pathways such as linoleic acid metabolism and glycerolipid metabolism were involved. All these ﬁndings suggested that L. reuteri treatment reversed the phenotype of ethanol-induced hepatitis and metabolic disorders. These findings provide evidence that L. reuteri might serve as a new therapeutic strategy for ALD.